Distribuição espacial de espécies arbóreas de cerrado: filogenia e traços de defesa contra herbivoria - Loiola, Priscilla de Paula (Universidade Federal de São Carlos, 2010)
Herbivory is expected to promote an overdispersed distribution of traits in co-occurring plant species, since similar plants are more vulnerable to specialised herbivores. As long as conservatism of traits is usually observed in lineages of plant species, phylogenetic relatedness may also be related to spatial distribution. Thus, we expected that defense traits against herbivory were conserved and that phylogenetic distances of co-occurring species were higher than expected by chance. In a cerrado site in southeastern Brazil, we analysed 100 quadrats, with 25 m 2 each, and sampled all woody individuals. For each species, we measured defense traits against herbivory and answered whether the degree of co-occurrence of species was correlated with both functional differences and phylogenetic distances. We also tested whether the defense traits were phylogenetically conserved. On the one hand, we did not find significant correlation between species co-occurrence and neither defense traits nor phylogenetic distances. On the other hand, we found phylogenetic signal for four out of nine defense traits. The absence of correlations may be due to (1) herbivory not being as strong as we expected in cerrado vegetation or (2) the presence of environmental filters, such as drought and nutrient-poor soil, promoting phylogenetic clustering, counteracting phylogenetic overdispersion by herbivory.
Keywords: Ecologia de comunidades; Cerrado; Traços funcionais; Herbivoria; Filogenia; Distribuição espacial; Traços de defesa; Cerrado; Defense traits; Herbivory; Phylogeny; Spatial distribution.; CIENCIAS BIOLOGICAS::ECOLOGIA